Penyuluhan Tentang Bahaya Penyalahgunaan Obat Bebas Dan Psikotropika di Kalangan Remaja - Pannyiwi, Rahmat; Nurlela, Lela; Kirana, Sukma Ayu Candra; Nurhaedah, Nurhaedah; Hastutiningtyas, Wahidyanti Rahayu (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The abuse of over-the-counter drugs and psychotropic substances among adolescents is a growing public health problem. Limited knowledge, high curiosity, and environmental influences are factors driving this risky behavior. This community service activity aims to provide health education to adolescents regarding the dangers of over-the-counter drug and psychotropic substance abuse. The implementation method was carried out through lectures, interactive discussions, and the distribution of educational leaflets. The results of the activity indicate an increase in adolescents' understanding of the negative impacts of drug abuse, as well as a growing awareness to avoid such behavior. This program is expected to be a preventative measure to reduce the rate of over-the-counter drug and psychotropic substance abuse among adolescents.